2000
DOI: 10.1128/iai.68.9.5284-5292.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Responses toTreponema pectinovorumandTreponema denticolain Human Gingival Fibroblasts

Abstract: Human gingival fibroblasts were challenged with Treponema pectinovorum and Treponema denticola to test three specific hypotheses: (i) these treponemes induce different cytokine profiles from the fibroblasts, (ii) differences in cytokine profiles are observed after challenge with live versus killed treponemes, and (iii) differences in cytokine profiles are noted from different gingival fibroblast cell lines when challenged with these treponemes. Three normal gingival fibroblast cell cultures were challenged wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 48 publications
4
34
0
2
Order By: Relevance
“…Ruby et al (23) recently reported that T. denticola can induce the production of IL-10 and a number of proinflammatory cytokines, such as IL-1␤, IL-6, IL-12 p70, and tumor necrosis factor, by macrophages. Nixon et al (21) demonstrated that T. denticola induced production of IL-6 and IL-8, but not MCP-1, by human gingival fibroblasts, while Treponema pectinovorum induced all three cytokines. Interestingly, our results showed that splenocytes from mice infected with T. denticola no longer produced IL-10 and had markedly decreased IFN-␥ production upon in vitro stimulation with T. denticola.…”
Section: Discussionmentioning
confidence: 99%
“…Ruby et al (23) recently reported that T. denticola can induce the production of IL-10 and a number of proinflammatory cytokines, such as IL-1␤, IL-6, IL-12 p70, and tumor necrosis factor, by macrophages. Nixon et al (21) demonstrated that T. denticola induced production of IL-6 and IL-8, but not MCP-1, by human gingival fibroblasts, while Treponema pectinovorum induced all three cytokines. Interestingly, our results showed that splenocytes from mice infected with T. denticola no longer produced IL-10 and had markedly decreased IFN-␥ production upon in vitro stimulation with T. denticola.…”
Section: Discussionmentioning
confidence: 99%
“…The surface molecules that showed enhanced IL-8 secretion were P. gingivalis gingipain-R (40), a glycoprotein fraction in the cell surface from P. intermedia (48), and a capsular polysaccharide from Actinobacillus actinomycetemcomitans (39). Several oral treponemes have been reported to stimulate proinflammatory cytokines in various cell types, such as gingival fibroblasts and gingival epithelial cells (2,25,37,43). However, with the exception of their LPS or LPS-like materials, none of them has been analyzed at the molecular level.…”
Section: Vol 73 2005 Induction Of Icam-1 and Cytokines By Spirochetmentioning
confidence: 99%
“…Oral treponemes have been observed to adhere to and invade connective tissues, as well as gingival epithelial cells (1,12,20,27), and also induce cytokine production from human gingival fibroblasts (18). Therefore, it is suggested that they play an important role in causing periodontal diseases.…”
mentioning
confidence: 99%